Role of smooth muscle Nox4-based NADPH oxidase in neointimal hyperplasia. (December 2015) - Tong, Xiaoyong; Khandelwal, Alok R.; Qin, Zhexue; Wu, Xiaojuan; Chen, Lili; Ago, Tetsuro; Sadoshima, Junichi; Cohen, Richard A.
Abstract: Elevated levels of reactive oxygen species (ROS) in the vascular wall play a key role in the development of neointimal hyperplasia. Nox4-based NADPH oxidase is a major ROS generating enzyme in the vasculature, but its roles in neointimal hyperplasia remain unclear. Objective: Our purpose was to investigate the role of smooth muscle cell (SMC) Nox4 in neointimal hyperplasia. Approach and results: Mice overexpressing a human Nox4 mutant form, carrying a P437H dominant negative mutation (Nox4DN) and driven by SM22α promoter, to achieve specific expression in SMC, were generated in a FVB/N genetic background. After wire injury-induced endothelial denudation, Nox4DN had significantly decreased neointima formation compared with non-transgenic littermate controls (NTg). ROS production, serum-induced proliferation and migration, were significantly decreased in aortic SMCs isolated from Nox4DN compared with NTg. Both mRNA and protein levels of thrombospondin 1 (TSP1) were significantly downregulated in Nox4DN SMCs. Downregulation of TSP1 by siRNA decreased cell proliferation and migration in SMCs. Similar to Nox4DN, downregulation of Nox4 by siRNA significantly decreased TSP1 expression level, cell proliferation and migration in SMCs. Conclusions: Downregulation of smooth muscle Nox4 inhibits neointimal hyperplasia by suppressing TSP1, which in part can account for inhibition of SMC proliferation and migration. Highlights: Provide direct evidence of smooth muscle Nox4 in promoting neointimal hyperplasia by using genetic knockdown of Nox4. Inhibition of smooth muscle Nox4 lessened wire-injury induced neointimal hyperplasia. Downregulation of Nox4 inhibited smooth muscle cell proliferation and migration by suppressing thrombospondin 1.